Iowa Ornithologists' Union, Quarterly field report, spring 1995 - Kent, Thomas H. (Thomas Hugh), 1934-et al; Iowa Ornithologists' Unionet al (1995)
Quarterly field report for the spring of 1995. It is published in Iowa Bird Life 65:69-79, 1995. Plustek - flatbed